Single Step Combustion Synthesis to Prepare Bismuth Titanate for Potential Apllications - Al-Amani, Umar (2012)

(untitled)
Bismuth titanate, Bi4Ti3O12 or BIT was systematically prepared by a single step combustion synthesis, and subsequently, sintered at different temperatures. In this work, the formation of corresponding phase with better degree of crystallinity was strongly affected by NH4OH and hydrolysis temperature. It was supported by XRD and Raman. Based on TG-DTA, the reaction was completely decomposed at around 500oC with larger exothermic peaks in the range of 250 – 300oC. The HRTEM micrograph showed clearly the agglomeration particles with irregular shape. Determination on sintering temperature was clearly showed by dilatometry curve whereby it was in the range of 800oC and above. The maximum relative density (86%) was achieved at 1000oC. The microstructure of BIT was randomly oriented, thus leading to a decrease in relative density. The conductivity of BIT was relatively high at elevated temperature, which can be explained in terms of larger grain size. Based on electrical measurement, the dielectric constant, dielectric loss, conductivity, resistivity, remanent polarization and coercive field of optimized BIT were recorded to be around 130 - 150, 0.00552 - 0.05212, 3.78 x 10-8 – 3.97 x 10-5 S/m, 2.52 x 104 – 2.64 x 107 Ω/m, 7 µC/cm2 and 30 kV/cm, respectively. In addition, the Curie temperature was approximately at 675oC.